Numerical modeling of the seismic performance of Romanian timber-framed masonry walls. (15th July 2021) - Parisse, F.; Poletti, E.; Dutu, A.; Rodrigues, H.
Highlights: Behavior of TFM structures is modeled with nonlinear springs at connections. Inverse fitting procedure is applied to calibrate the numerical cyclic response. Comparison of seismic performance between Pombalino and Romanian systems. Abstract: Traditional architecture with timber-framed masonry (TFM) system was used in many countries prone to seismic events due to its earthquake-resistant performance. In this context, Romanian TFM buildings were constructed by local builders applying non-engineered measures to reduce seismic vulnerability. However, the seismic safety assessment of these buildings still presents open issues due to material modeling, and in simulating the complex interaction between structural elements. Although the seismic response at building scale depends on a combination of factors such as geometry, boundary conditions, quality of construction, structural connections and interactions, it is significantly influenced by the in-plane behavior of TFM walls. The present paper aims to investigate the seismic performance of Romanian TFM walls by using a simplified equivalent frame model, in OpenSEES software, with linear elastic elements and nonlinear behavior lumped at the connections. Indeed each joint is modeled with nonlinear springs, one per degree of freedom, for which the parameters were initially calibrated based on representative experimental tests in literature. After this calibration, the resulting parameters were updated to approach the local and global responses from the experimental campaign performed at the Technical University of Civil Engineering of Bucharest in terms of initial stiffness, maximum base shear, and total dissipated energy. The simplified modeling strategy requires limited computational efforts and provides information about the role of each connection.